Factors Affecting Mobile Banking Satisfaction: A Case Study of Bank Syariah Indonesia - Islah, Elisa Imamil; Nuriyah, Aminah (Universitas Mercu Buana, 2024)
Main Objective The purpose of this study was to determine the effect of efficiency, fulfilment, system availability, privacy, responsiveness, feature and reliability to customer satisfaction study case in Indonesia Sharia Bank in JABODETABEK. Method This research uses a descriptive quantitative approach with a case study of PT.Bank Syariah Indonesia in JABOBETABEK costumer. The data collection technique was obtained from distributing questionnaires via google form and the data was processed using software. By using multiple linear regression analysis. Key Findings The results showed that the seven variables had a significant effect on mobile banking customer satisfaction. The strongest dimensions in explaining the quality of BSI mobile services are feature, reliability, and privacy, respectively. Factors affecting reliability and feature variables have the strongest influence on mobile banking customer satisfaction. Theoretical and Practical Implications The results of this study show that system vailability and responsiveness have no effect on mobile banking customer satisfaction, indicating that customer satisfaction is not directly influenced by the BSI mobile system which is not the main factor taken into consideration by customers in using the mobile BSI.